COVID-19 and Substance Use Disorders: Recommendations to a Comprehensive Healthcare Response. An International Society of Addiction Medicine Practice and Policy Interest Group Position Paper - Farhoudian, Ali; Baldacchino, Alexander; Clark, Nicolas; Gerra, Gilberto; Ekhtiari, Hamed; Dom, Geert; Mokri, Azarakhsh; Sadeghi, Mandana; Nematollahi, Pardis; Demasi, Maryanne; Schütz, Christian G; Hash-Emian, Seyed Mohammadreza; et al. (Basic and clinical neuroscience, 2020)
Coronavirus Disease 2019 (COVID-19) is escalating all over the world and has higher morbidities and mortalities in certain vulnerable populations. People Who Use Drugs (PWUD) are a marginalized and stigmatized group with weaker immunity responses, vulnerability to stress, poor health conditions, high-risk behaviors, and lower access to health care services. These conditions put them at a higher risk of COVID-19 infection and its complications. In this paper, an international group of experts on addiction medicine, infectious diseases, and disaster psychiatry explore the possible raised concerns in this issue and provide recommendations to manage the comorbidity of COVID-19 and Substance Use Disorder (SUD).